Development of a transdisciplinary education concept to prepare textile technology students for dealing with AI - Lennart Hellweg; Johanna Bulthaupt; Alen Tabakovic; Mathias Beer (Communications in Development and Assembling of Textile Products, 2024)
A basic understanding of the mechanisms and implications of the use of Artificial intelligence (AI) is crucial to effectively implement AI in business and society. To achieve this goal, the research project described here aims to provide students from different disciplines with practical AI knowledge. Instead of focusing on traditional teaching approaches, students work together on transdisciplinary and interdisciplinary projects. The basis here is provided by department-specific application scenarios. Supported by learning nuggets, expert lectures and an accessible software infrastructure, students thus gain easy access to AI topics. The goal in the Faculty of Textile and Clothing Technology is to train specialists in the use of AI in the textile process chain. Students will learn how to classify image data of fibers based on a practical example. Among other things, they will generate a data set for a neural network and work closely with computer science students to implement it. The focus is on enabling students to apply AI independently and thus create the basis for new innovative ideas in industry